Climatization: A critical perspective of framing disasters as climate change events - Stephen Grant; Charlotte Crim Tamason; Peter Kjær Mackie Jensen (Climate Risk Management, 2015)
In recent years, there has been a developing trend of labelling some disasters as ‘climate change disasters’. In doing so, a discursive phenomenon can emerge that the authors have coined ‘climatization’ which is specified as framing a disastrous event or degraded environmental condition as caused by climate change, in order to reach an intended goal or to distract the discussion from the real problem which might have a different root course than caused by the climate change effects. The implications of climatization are currently unclear – particularly to what extent climatizing a disaster might increase or decrease the vulnerability of a population at risk of disaster. The purpose of this paper is thus to open up the concept of climatization to investigation, and examine what affect such a discursive framing might have on public and political perception. Climatization is here discussed in the context of Bangladesh – a country that is expected to be among the worst affected by climate change and a country in which some people claim the effects of climate change can already be seen. A qualitative field study which included key informant interviews, focus group discussions and a literature review was conducted in Bangladesh. The study found recent examples of climatization related to Cyclone Aila (2009) and salt water intrusion in Bangladesh. In most cases these disasters were climatized in order to create a sense of urgency in order to push for an increase in financial aid to Bangladesh and to deflect responsibility for inaction that led up to the disaster. This study urges caution as there is a potential for climatization to be used as a means to cover up negligence or bad management and there is a risk that by climatizing a disaster key vulnerabilities may be overlooked.